Os tipos das plantas vasculares do herbário da Universidade Rural do Estado de Minas Gerais (VIC) : II- Asclepiadaceae, Ebenaceae, Solanaceae - R Vidal, Maria Rosária; Nunes Vidal, Waldomiro (Revista Ceres, 2025)
This paper consists of a selection of types of the Asclepiadaceae, Ebenaceae e Solanaceae families, from the Viçosa herbarium (VIC). Transcriptions ofthe original descriptions were made, thereby attempting to establish the categories of the types existing in the herbarium.